Momento do Sim: Plano de Aplicação Transmídia para o setor de Eventos - Experimentações no mercado de casamentos em Uberlândia - Batista, Carolina Tomaz (2016)
In media convergence times of the storytelling and celebrate important moments of life has changed. The stories are no longer counted only around the fire, and the festivals and events, to keep track with a Polaroid, small balloons and brigadiers. Many of these changes are due to technological developments, intensified with the spread of the internet. In today's society, the stories also spread by social media, for games, movies and books, that is, the narrative now flow by the media and behave in accordance with the vehicle in which they are transmitted. The public, which is a multimedia, whatever their stories and celebrations also are. From the convergence of public profile, the creation possibilities that transmedia storytelling and seeking to create a production that can fit the new profile of the company is that there is the proposal to create the implementation plan for the event sector of the city of Uberlândia, MG. In order to exemplify, organize the proposal and demonstrate the possibilities of the proposed plan, the market of weddings has been selected for production, earning the name “Momento do Sim”. The following report presents as was the construction and development of the implementation plan. It shows the step plan planning, specific transmedia universe created for the wedding industry and the media and selected products to make the contract to plan an event like marriage in an innovative and practical way.